Degree of Possessing Critical Thinking Skills by Students of Faculty Science and Arts Ola Depending on Test California 2000 - Ahmad Al-Qawasmeh (My University, 2014)
The study aimed to identify the degree possession of students of the Faculty of Arts and Sciences Ola critical thinking skills where the study sample consisted of 380 students, In order to achieve the main objective of the study, the researcher used California to test the skills of critical thinking model (2000), after verification of its psychometric properties, and suitability for Saudi Arabia and the environment that were considered appropriate for the purposes of scientific research in order to answer questions from the study, The findings showed that the skill of reasoning came in the first rank among other critical thinking skills. Next, was the skill of induction, followed by the skills of analysis, evaluation and finally came the skill of concluding. Moreover, the results showed that there were statistical significance differences in the level of critical thinking skills and they could be attributed to of sex variable and in favor of female students. The findings also revealed that there weren't statistical significance differences in the level of critical thinking skills due to the variable of specialty.

هدفت الدراسة التعرف الى درجة امتلاك طلبة كلية العلوم والآداب بالعلا لمهارات التفكير الناقد حيث تكونت عينة الدراسة من (380) طالبا وطالبة، ولتحقيق الهدف الرئيسي للدراسة استخدم الباحث اختبار كاليفورنيا لمهارات التفكير الناقد نموذج (2000) بعد التحقق من خصائصه السيكومترية، وملاءمته للبيئة السعودية والتي اعتبرت مناسبة لغايات البحث العلمي من اجل الاجابة عن اسئلة الدراسة، وأظهرت النتائج: أن مهارة الاستدلال احتلت المرتبة الاولى بين مهارات التفكير الناقد يليها مهارة الاستقراء فالتحليل والتقييم وأخيراً الاستنتاج، كما أظهرت النتائج وجود فروق ذات دلالة احصائية في مستوى مهارات التفكير الناقد تعزى لمتغير الجنس ولصالح الطالبات وأظهرت النتائج ايضاعدم وجود فروق ذات دلالة احصائية في مستوى مهارات التفكير الناقد تعزى لمتغير التخصص.
درجة امتلاك طلبة كلية العلوم والآداب بالعلا لمهارات التفكير الناقد تبعاً لاختبار كاليفورنيا (2000)